Synthesis of biodiesel from soybean oil using zinc layered hydroxide salts as heterogeneous catalysts - Reinoso, Deborath Mariana (2014)
In this work, the transesterification of soybean oil with methanol using layered heterogeneous catalysts to produce biodiesel was studied. The zinc hydroxy acetate salt Zn5(OH)8(CH3COO)2·4H2O (abbreviated Zn–Ac) and the zinc hydroxy nitrate salt Zn5(OH)8(NO3)2·2H2O (abbreviated Zn–Nit), which have a layered structure, were synthesized (chemical precipitation) and characterized by X-ray diffraction, infrared spectroscopy, scanning electron microscopy, particle size distribution measurements, specific surface area determination and thermogravimetric analysis. Zn–Ac and Zn–Nit were tested in the transesterification of soybean oil at 100 °C for 2 h. Zn–Nit presented 83.9% oil conversion with 51.5% FAME yield, and it was stable in three consecutive tests, showing good tolerance to aqueous content. Zn–Ac was not stable. The salts transformed into Zn glycerolate at 140 °C in the reaction medium.